SCALING UP OF LACTIC ACID FERMENTATION USING Enterococcus faecalis - EIVO, KELVIN (Universiti Malaysia Sarawak (UNIMAS), 2018)
Enterococcus faecalis is a Lactic Acid bacterium and was used to scaling up a lactic acid fermentation (LAF) from laboratory scale to pilot scale. Scaling up of LAF as the preferred embodiment of industry is a major concern in this study. Develop a large scale of LAF always became a huge challenge because of scarce data is available in large scale. LAF is studied in order to scale up the fermentation process from 3-litre bioreactor fermenter to 100-litre open stirred tank reactor (STR). Fermentations in batch mode for Lab and Pilot scales results were compared in terms of productivity, and yield by following the kinetics of the growth, lactic acid production, and glucose consumption. The fermentations were performed at pH 6.86, 45 C, and 100 rpm. Lactic acid (LA) produced by the strain was titrated in situ using 10M NaOH. Simulation of the fermentation was conducted by using SuperPro Software and data from pilot scale. The results of the fermentation for both scales were analysed and compared using t-test and ANOVA. The results showed the production rate for laboratory scale of laboratory 1, 2 and 3 is 5.06 g/L·h, 4.97 g/L·h, and 4.84 g/L·h respectively. While for pilot scale, the production rate of Pilot 1 and Pilot 2 is 1.53 g/L·h and 3.91 g/L·h respectively. The yield for laboratory 1, laboratory 2, laboratory 3, pilot 1 and pilot 2 is 0.93, 0.94, 0.93, 0.92 and 0.91 respectively. After comparing the production rate between laboratory and pilot scale using ANOVA, it was found that, there is no significant difference between both processes. Therefore, the LA production rate of pilot scale was the same as laboratory scale using Enterococcus faecalis bacteria.